Pengaruh K3 (Keselamatan Dan Kesehatan Kerja) Dan Pelatihan Terhadap Kinerja Karyawan: (Studi Pada PT PLN (Persero) Ulp Kotapinang) - Sianturi, Hanatul Fitri; Siregar, Onan Marakali (Universitas Sam Ratulangi, 2023)
This study aims to analyze the influence of K3 (Occupational Safety and Health) and training on employee performance at PT PLN (Persero) ULP Kotapinang. Influence K3 (Occupational Safety and Health) and training are partially and simultaneously analyzed on employee performance. Sampling used a saturated sample technique and used 30 respondents. The analysis methods used are the validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis test. The results of this study showed that K3 (Occupational Safety and Health) had a significant positive effect on employee performance, obtained a t-count value of 3,299>2,052 with a significant value of 0.003< 0.05 and had a regression coefficient value of 0.311. Training also had a significant positive effect on employee performance obtained a t-value of 3,635>2,052 with a significance level of 0.001 and had a regression coefficient value of 0.255. In simultaneous testing, the K3 (Safety and Health) variable and training had a simultaneous effect with a magnitude of 55.4%, while the remaining 44.6% was influenced by factors outside the variables of this study.